Peningkatan Strategi Pemasaran Jamur di Kampung Jamur Limau Manis - Syafrika Deni Rizki; Febri Hadi; Muhammad Afdhal (Jurnal Pengabdian Masyarakat Dharma Andalas, 2022)
This study aims to determine the marketing channels of mushrooms, to know the internal and external factors of the mushroom marketing business, to know the marketing strategies of mushrooms. From the results of the SWOT analysis, it is known that the internal factors (strengths and weaknesses) and external factors (opportunities and threats) of the mushroom business in sweet limes. Its strengths are: Good mushroom quality, Affordable amount of capital, Competitive pricing, Retaining customers. Weaknesses are: There is still a lack of promotional activities, Lack of a marketing system, The production process still uses simple technology. The opportunities are: The market share of oyster mushrooms is still wide, Mushrooms can be processed into derivative products, Government intervention. The threats are: There is competition between mushroom cultivators, the effect of changing seasons/weather, the marketing strategy that can be done by mushroom farmers is aggressive growth (growth oriented strategy), namely by expanding the share, and through increasing added value by processing products from these mushrooms.